1999
DOI: 10.1590/s0100-06831999000100022
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fractions in the microbial biomass in soils of southern Brazil

Abstract: SUMMARY RESUMO: FRAÇÕES DO NITROGÊNIO NA MICROBIOTA DE SOLOS DO SUL DO BRASIL A reação de compostos nitrogenados com a ninhidrina pode ser utilizada como parâmetro indicador dos produtos citoplásmicos oriundos da lise de células microbianas mortas pela fumigação. Com base nessa assertiva, realizou-se o presente trabalho, em 1996, com o objetivo de avaliar as concentrações de N-total, N-reativo com ninhidrina (NR-N), N-amônio (A-N) e N-a-amino presentes na biomassa microbiana de solos do Rio Grande do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to Camargo et al (1999), under conditions that favor the proliferation of microbial biomass, the hexosamine-N content in the soil increases, but over time it may decrease with the limitation of the substrate. González-Prieto et al (1997) observed decrease in the contents of this fraction after application of mineral fertilization in maize and pasture, suggesting that this form is part of an initial active pool of mineralizable N, which is related to the transitory increase in the soil microbial population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Camargo et al (1999), under conditions that favor the proliferation of microbial biomass, the hexosamine-N content in the soil increases, but over time it may decrease with the limitation of the substrate. González-Prieto et al (1997) observed decrease in the contents of this fraction after application of mineral fertilization in maize and pasture, suggesting that this form is part of an initial active pool of mineralizable N, which is related to the transitory increase in the soil microbial population.…”
Section: Resultsmentioning
confidence: 99%
“…The application rate of 50 m 3 ha -1 exceeds the MF in all the soil layers evaluated, and application rates greater than or equal to 100 m 3 ha -1 up to the 5 cm depth and 200 m 3 ha -1 in the 5-10 and 0-10 cm layers lead to the greatest contents of this N fraction in the soil (Table 5). This form of N is present in amino acids which make up proteins that underwent a peptide bond during protein synthesis (Camargo et al, 1999) where N is bound to the alpha group of the carbon, with high bonding energy by hydrogen bridges, Van der Waals forces, and covalent complexes to humic colloids (Stevenson, 1994). González-Prieto and Carballas (1991) observed a decrease in the α-amino-N fraction in cropped soils when compared to natural soils, suggesting that this form may be easily mineralizable and potentially available to plants.…”
Section: Resultsmentioning
confidence: 99%
“…However, the MBN as a percentage of TN obtained are lower than the ranges reported in MBC/MBN MBC/OC MBN/TN literature by other workers for arable, pasture and forest; and the low values indicate that the microbial biomass is not important as a sink for N in these areas [27]. Differences in biomass content are directly related to the primary factors affecting microbial ecology [31]. Climatic factors play significant role on biodegradable organic material and microbial growth [32].…”
Section: Effect Of Land Use On Soil Microbial Biomass Ratiomentioning
confidence: 77%
“…This result may be related to climate factors (Figure 1) during the experimental time, as the first cycle presented an imbalance relative to qCO 2 although it promoted a higher BSR value. According to Cattelan and Vidor (1990), this variable can be influenced by factors such as humidity, temperature, and soil nutrient availability. UB S , CJs, and the intercrop systems UBCJ I , UBCE I , and PGCJ I were grouped with the highest means of MBC in the first cycle, while CE S , MA S , UBCE I , and PGCE I were the cover crops that most favored MBC in the second cycle (Table 1).…”
Section: Resultsmentioning
confidence: 99%